2014
DOI: 10.1155/2014/524286
|View full text |Cite
|
Sign up to set email alerts
|

Valsalva Retinopathy Associated with Sexual Activity

Abstract: A 54-year-old healthy male presented complaining of sudden loss of vision in the right eye. Initial visual acuity was counting fingers. The patient's acute vision loss developed after sexual activity. Color fundus photos and fluorescein angiography were performed showing a large subinternal limiting membrane hemorrhage in the macular area. A 23-gauge sutureless pars plana vitrectomy with brilliant blue assisted internal limiting membrane peeling was performed with best-corrected visual acuity recovery to 20/50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A significant increase in intravenous pressure in all of the body during Valsalva maneuver increases the risk of bleeding in all body parts including the retina. The relationship between sexual activity and bleeding in the retina is reported in other studies such as the study conducted by Freiberg et al (33) Therefore regarding to mentioned studies, considering correct lifestyle is beneficial in eye health maintenance and prevention of its diseases.…”
Section: Jamshid Shayanfar Etal Eye and Its Health From The Viewpoint...mentioning
confidence: 66%
“…A significant increase in intravenous pressure in all of the body during Valsalva maneuver increases the risk of bleeding in all body parts including the retina. The relationship between sexual activity and bleeding in the retina is reported in other studies such as the study conducted by Freiberg et al (33) Therefore regarding to mentioned studies, considering correct lifestyle is beneficial in eye health maintenance and prevention of its diseases.…”
Section: Jamshid Shayanfar Etal Eye and Its Health From The Viewpoint...mentioning
confidence: 66%
“…Sexual intercourse can be the source of various hormonal, hematological, and mechanical changements on the hemodynamic system of the organism, which can be a risk factor for valsalva retinopathy [ [10] , [11] , [12] , [13] , [14] ].…”
Section: Clinical Discussionmentioning
confidence: 99%
“…It usually occurs secondary to valsalva's maneuver, a forcible exhalation effort against a closed glottis, causing a sudden rise in intrathoracic pressure. 5 It has previously been reported that Valsalva retinopathy can occur due to a variety of causes, such as vomiting, the lifting of a heavy object, the physical strain that occurs during child birth and general anesthesia. 6 Patients with Valsalva retinopathy can be managed conservatively with careful prognosis following failed laser treatment.…”
Section: Discussionmentioning
confidence: 99%